Presence of obestatin in breast milk: Relationship among obestatin, ghrelin, and leptin in lactating women - Aydin, Suleyman; Ozkan, Yusuf; Erman, Fazilet; Gurates, Bilgin; Kilic, Nermin; Colak, Ramis; Sahn, Ibrahim (Elsevier Science Inc, 2008)
Objective: The peptide hormones ghrelin and leptin have been found in blood and breast milk. This study was undertaken to investigate whether breast milk also contains obestatin, which is derived from the same gene as ghrelin but has opposite actions, and to characterize the relations among serum and milk ghrelin, obestatin, and leptin levels in lactating mothers. Methods: Venous blood, colostrum, and mature milk were obtained from healthy lactating women (n = 31) just before suckling. The ghrelin and obestatin concentrations were determined by radioimmunoassay. Leptin levels were measured by enzyme-amplified sensitivity immunoassay. Results: Obestatin levels in colostrum (538.9 pg/mL) and mature milk (528.5 pg/mL) were more than twice the corresponding blood levels (270.3 and 289.4 pg/mL, respectively). In contrast, leptin levels in colostrum (2.01 ng/mL) and mature milk (2.04 ng/mL) were more than five-fold lower than the corresponding blood levels (11.54 ng/mL). There was no correlation between breast milk ghrelin levels and leptin (r = - 0.18, P > 0.05). However, there was a positive correlation between leptin levels in breast milk and blood (r = 0.369, P < 0.05). Conclusion: The origin of milk obestatin is not currently known, but it comes from the blood or breast and may drain through the mammary glands into the milk. Ghrelin, obestatin, and leptin in the milk may directly affect appetite and their levels may be related to the regulation of energy balance and the pathogenesis of obesity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: obestatin; ghrelin; leptin; breast milk; serum